Solid State Electrochemistry I 2009
DOI: 10.1002/9783527627868.ch7
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Metal Cation and Proton Conductors: Relationships between Composition, Crystal Structure, and Properties

Abstract: The aim of this chapter is to provide an overview of materials where fast transport of alkali metal cations and protons is observed. A general discussion of factors affecting conductivity and techniques used to study ion migration paths is followed by a review of the large number of cation conductors. Materials with large alkali ions (Na-Cs) are often isostructural and therefore examined as a group. The lithium conductors with unique crystal structure types and proton conductors with unique conduction mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 277 publications
(335 reference statements)
0
9
0
1
Order By: Relevance
“…It has been confirmed that the high electronegativity of the octahedral cations in oxides is the main factor stabilizing prismatic structures. 35,36 The electronegativity of Mn 2+ (1.436) is higher than that of Mg (1.208). 37 It can be understood that the heavily Mn 2+ -doped Na 2 CaMg(PO 4 ) 2 could be stable with the prismatic structure (b-phase).…”
Section: Discussionmentioning
confidence: 98%
“…It has been confirmed that the high electronegativity of the octahedral cations in oxides is the main factor stabilizing prismatic structures. 35,36 The electronegativity of Mn 2+ (1.436) is higher than that of Mg (1.208). 37 It can be understood that the heavily Mn 2+ -doped Na 2 CaMg(PO 4 ) 2 could be stable with the prismatic structure (b-phase).…”
Section: Discussionmentioning
confidence: 98%
“…For the majority of the materials mentioned in Ref. [] no crystallographic data was collected. Especially for the materials systematised under the ‘Brucite‐like’ structures, conductivity data is presented without structural information.…”
Section: Methodsmentioning
confidence: 99%
“…As taken from Ref. [], the best‐conducting crystalline solid Na‐ion electrolytes known so far can be categorised into three different main groups (β‐alumina, NaSICon and Na rare‐earth silicates) showing very similar, comparably high conductivities for Na + (approx. 10 −3 S/cm at room temperature, around (10 −2 –10 0 ) S/cm at 300 °C).…”
Section: Introductionmentioning
confidence: 99%
“…Polarizable anion frameworks or anisotropic polarizability of the anions enhance the migration of Li ions [21,22]. The chemical properties further depend on the material, structural and experimental properties mentioned above [23,24].…”
Section: Introductionmentioning
confidence: 99%